A proposta curricular de ciências em Minas Gerais e as práticas docentes - Vanubia Emanuelle de Souza (2010)
In this project we tried to identify the teaching methods and learning strategies used by middle school science teachers by the implantation of the curricular proposal of this discipline in some public schools of Minas Gerais on Pirapora district. This is a research of qualitative character that has the objective of establishing a dialog between the official documents of the State Educational Department of Minas Gerais SEE/MG and the practices executed by the teachers in their classrooms, sustained by Tardifs (2010) references about teachers knowledge and the formation of professional educators (DELIZOICOV, 2007; SHULMAN, 1997). By this, our purpose is to investigate the implantation of the science curricular reformation on the school and how teachers would deal with the changes. For that we followed up two teachers routine for three months on different schools and classes, with the attempt to figure out their teaching methods and learning strategies. These teachers were chosen from a group of initially twelve educators, who had the right profile for this study, in other words, teachers who were identified with the science curricular proposal, who by their declarations agreed to have their information on our research. Four teaching sequences were planned and executed by analyzed teachers and also used by us to collect data for our research on this work, which totalizes sixty hours of direct observations in the classrooms. We identified a harmony on the practices of the analyzed teachers which reflects the guidelines of the science curricular proposal and a greater diversification of teaching strategies according to the content ministered in class. The teachers participation on the proposals elaboration favored a better identification and acceptance for part of the educators on Minas basic education dynamics (re)structure. Despite this, we believe that the continual formation is not hinged to the school every day, the changes needed will be diminished . The results tell that teaching practices cannot be faced as a mere technical exercise marked by the attendance of prescription curricular developed by others. The personal and professional profile of the teachers cannot be considered on an isolated form, but yes like a product of the school culture that they belong to. While being transported to the classrooms, the education politics are reconstructed to be adapted to the characteristics of each school culture. Another note is that the teaching practice doesnt consist in a space of application of knowing: the teachers are subjects of knowledge and holders of a specific, relative knowledge to their educators (TARDIF, 2010), from there, the necessity in the teachers to go up in value like changes agent and like professional got involved in their growth. In other words: the quality claimed for the teaching begins with the formation of the teachers.